"Eu tive que me reinventar": mulheres com lesão medular adquirida e modos de (re)construírem a si mesmas e a suas vidas sexuais. - Morais, Raissa Maria Bittencourt de (2018)
This study aimed to understand how women who suffered an acquired spinal cord injury (re)construct themselves and their sexual lives. The medullary lesions (ML) are all injuries that affect the structures contained in the spinal canal and can lead to motor, sensory, autonomic and psychoaffective alterations. It is one of the situations that can most affect the life of any individual and that can bring with it many biopsychosocial repercussions. The research that serves as the basis to this dissertation is of qualitative character and is founded theoretically and methodologically in the writings of Michel Foucault and of other authors that dialogue with his thought. As methodological strategies, the Narrative Interviews and the Field Diary were used as tools for the construction of the narratives of the women with acquired spinal cord injury, which were analyzed through a descriptive analytics of the subject of Foucauldian inspiration. These analysis have pointed out that these women are crossed by diverse discursive formations, institutions, knowledge/power games that constitute them as capable of organizing their own methods and ways to perform a sexual life satisfactorily in the way it is possible to live it. The condition of woman, the exercise of a sexual life after a trauma or accident, and the way in which they act upon their subjectivity showed themselves as difficult paths; it is evident the importance of looking at sexuality as a dispositif; it is emphasized the existence of a society that considers certain bodies, and here the bodies with spinal cord injury, as abjects and the suffering experienced by each one of them is verified when faced with the change of an accepted body. Thus, in the narratives we find the certainty that women with acquired spinal cord injury are not considered as asexual, on the contrary, all of them reported experiencing - or having lived - one or more loving, affective and sexual relationships. We hope that our research will contribute to the broadening of women's voices and struggles as well as to the greater opening of spaces for dialogue on the subject of sexuality in what concerns people with physical disabilities, especially women with acquired spinal cord injuries.